From no to yes (London : Video Arts, 1991)
This video deals with the art of persuasion. An art that must learnt by anyone running meetings or influencing others if the road to agreement is not to be strewn with acrimony, conflict-and in this case high blood pressure
Bibliographical information is taken from the publisher's catalogue
Keywords: Negotiation; Persuasion (Psychology)